Multi-band propagation of spoof surface plasmon polaritons by its high-order modes. (1st July 2022) - Zhu, Shuangshuang; Wen, Pin; Liu, Yuhuai
Abstract: Compact dual-band and tri-band bandpass filters (BPFs) based on high-order modes of spoof surface plasmon polaritons (SSPPs) are proposed. By using the meander line technique, the electrical size of the proposed SSPP structure was reduced by 68% compared with the traditional rectangular-grating SSPP structure. The high-efficiency passbands are excited by high-order modes of SSPPs. Therefore, dual-band and tri-band BPFs are designed by using two and three high-order modes of SSPPs, respectively. In addition, a notched band is obtained by loading three complementary split-ring resonators (CSRRs) on the bottom layer of the tri-band BPF. Thus, a quad-band BPF is achieved.